Distanciamiento de siembra con dos fertilizaciones inorgánicas en el rendimiento de forraje de Canavalia ensiformis L. “Canavalia” en Zungarococha, Perú – 2023 - Cotrina Mendoza, Irvin Lenner (2025)
Protein production with Fabaceae species is one of the most economical alternatives available to cattle farmers for feeding their livestock. The research is titled SOWING SPACING WITH TWO INORGANIC FERTILIZATIONS ON FORAGE YIELD OF Canavalia ensiformis L. “CANAVALIA” IN ZUNGAROCOCHA, PERU - 2023, carried out in the experimental field of the Faculty of Agronomy of the National University of the Peruvian Amazon under a Randomized Complete Block Design with a factorial arrangement of 2 x 2, where the treatments were T1 = F1D1 (20N - 20P2O5 - 20 K2O + 0.5 m x 0.5 m), T2 = F1D2 (20N - 20P2O5 - 20 K2O + 1.0 m x 0.5 m), T3 = F2D1 (Bayfolan blue soil + 0.5 m x 0.5 m) and T4 = (Bayfolan blue soil + 1.0 m x 0.5 m), reaching the following results that there was no interaction between fertilizers and planting spacing, the T3 Spread (F2D1 = BAYFOLAN BLUE SOIL + 0.5 m X 0.5 m), in the present investigation gave the best results with respect to the other treatments with a green matter of 2.82 kg/m2, dry matter of 0.73 kg/m2, green leaf matter of 1.19 kg/m2, green stem matter with 1.63 kg/m2 and with a yield per hectare of 28,200 kilos per hectare.